Cultura de Segurança do Paciente na Ótica da Enfermagem em uma Unidade de Transplante Renal - Câmara, Janaína de Jesus Castro (2016)
The patient safety culture in the hospital environment is listed as one of the phenomena that can provide an effective and safe care. There is a need that the safety culture should be measured in order to determine the strengths and fragile points for patient safety. This study aimed to evaluate the patient safety culture from the perception of the nursing team in a Renal Transplant Unit. It is a descriptiveexploratory with a quantitative approach, conducted with 25 participants in renal transplant unit of a public teaching hospital in the city of São Luís, Maranhão, Brazil. The data collection occurred during the months of May and June 2015, by means of the application of the questionnaire Hospital Survey on Patient Safety Culture - HSOPSC. Descriptive statistics was used to classify the dimensions in areas of strong and weak, and inferential statistics to test the instrument reliability Cronbach Alpha, to the characteristics of the participants the Chi-Square test, mean and frequency, and the correlation of the dimensions of the Spearman Correlation Coefficient. The study considered fully the ethical and legal precepts of Resolution no. 466/12. The Cronbach Alpha calculated ranged from 0.13 to 0.97, demonstrating the instrument reliability. In relation to the participants the majority were 10 nurses (40%), female 23(92%), 12 (48%) concluded lato sensu graduate, age was 9 (36%) between 36 and 40 years, 11 (44%) worked in the institution from 11 to 15 years, 12 (48%) have between 11 and 15 years in the unit and 20 (80%) work of 20 to 39 hours per week. As far as the classification in variable working unit, the dimension 'team work within units “presented the highest percentage of positive answers in 100 (77%), being considered the single area of strength for patient safety. Already the predominantly fragile area for patient safety was the dimension “Non punitive responses to errors” of 75 (24%) responded positively. In relation to the variable hospital organization, only the dimension “internal transfers and passages on duty” portrayed highest score of 100 (57%) with positive responses. For the variable outcome measures, the two dimensions showed percentages bitterly negative, “general perception of patient safety “with 100 (45%) and “frequency of notified events” was the most negative percentage of all sizes corresponding to 75 (58%). As the most significant correlation was demonstrated between the variables unit of work and organizational structure, in the association of dimension “organizational learning and continuous improvement” with “team work between the units” (r = 0.70453,  - Value = <0. 0001). The study highlights the existence of a culture of punishment and guilt, underreporting of events, work overload which are the main challenges for safe care.